Kinesiotherapy as a method supporting the rehabilitation of lumbosacral spine pain in pregnant women - Dąbrowska, Maria; Lisecki, Jakub; Biernacki, Maciej; Paruszewska-Achtel, Monika; Ulenberg, Agata; Ulenberg, Grzegorz (Journal of Education, Health and Sport, 2019)
During pregnancy, a number of changes take place in the woman's body. They often cause pain in the spine, especially the lumbosacral segment. Dynamic slicing supports the rehabilitation of women during pregnancy, thanks to the fact that it has an analgesic effect, improves the flow of limes and increases the elasticity of tissues. Kinesiotherapy included in the rehabilitation is an effective method of pain relief in this area in pregnant women.